2008
DOI: 10.1002/mrm.21869
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging quantification of left ventricular dysfunction following coronary microembolization

Abstract: Microembolization is common after coronary interventions, and therefore this MRI study aimed to quantify the effect of coronary microembolization on left ventricular (LV) function. The left anterior descending artery (LAD) was selectively catheterized in an XMR suite (Philips Medical Systems, Best, The Netherlands) in eight pigs to deliver MR contrast media to measure the LAD territory using first-pass perfusion and for intracoronary delivery of the embolic agent. Cine, tagged, and delayed contrastenhanced MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Eight adult healthy farm pigs (mean weight, 33 kg 6 1 [standard error of the mean ]) were anesthetized with a mixture of 2%-5% isofl urane and oxygen at a rate of 2-3 L/min, as described previously ( 8,9 ). Two animals died within 24 hours after delivery of the embolic materials.…”
Section: Study Protocol and Microembolimentioning
confidence: 99%
See 1 more Smart Citation
“…Eight adult healthy farm pigs (mean weight, 33 kg 6 1 [standard error of the mean ]) were anesthetized with a mixture of 2%-5% isofl urane and oxygen at a rate of 2-3 L/min, as described previously ( 8,9 ). Two animals died within 24 hours after delivery of the embolic materials.…”
Section: Study Protocol and Microembolimentioning
confidence: 99%
“…Microinfarcts are defi ned as bright heterogeneous subregions seen on delayed contrast material-enhanced MR images and pale unstained necrotic subregions seen on histochemically stained specimens (8)(9)(10)(11). In several studies, researchers found heterogeneous microinfarcts in patients ( 2,5,12,13 ) and animals (8-11) on delayed contrastenhanced MR images.…”
Section: Study Protocol and Microembolimentioning
confidence: 99%
“…[2] Furthermore, CME can also lead to progressive myocardial malfunction, including overt myocardial infarction, contractile dysfunction, arrhythmias and coronary reserve reduction. [4,5] Once CME occurs, clinical outcomes of such patients are not improved by using coronary thrombolysis agents, nitroglycerin and platelet GPIIb/IIIa receptor antagonists or direct thrombectomy. [6,7] Therefore, therapy for CME remains an issue and furthermore, the underlying molecular mechanisms of pathophysiology in CME remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…XMR suites typically have become more available, with various vendors offering dual-modality solutions. [1][2][3][4][5][6][7][8][9][10][11][12][13] These systems combine the three-dimensional imaging capabilities and excellent soft tissue contrast provided by MR with the high spatial/temporal resolution and accurate device tracking provided by x ray. To eliminate system compatibility concerns, the suites typically have long travel distances between MR and x-ray components.…”
Section: Introductionmentioning
confidence: 99%